Thymoglobulin induction in heart transplantation: patient selection and implications for maintenance immunosuppression - Zuckermann, Andreas; Schulz, Uwe; Deuse, Tobias; Ruhparwar, Arjang; Schmitto, Jan D.; Beiras‐Fernandez, Andres; Hirt, Stephan; Schweiger, Martin; Kopp‐Fernandes, Laurenz; Barten, Markus J. (Transplant international, 2015)
Clinical data relating to rabbit antithymocyte globulin (rATG) induction in heart transplantation are far less extensive than for other immunosuppressants, or indeed for rATG in other indications. This was highlighted by the low grade of evidence and the lack of detailed recommendations for prescribing rATG in the International Society for Heart and Lung Transplantation (ISHLT) guidelines. The heart transplant population includes an increasing frequency of patients on mechanical circulatory support (MCS), often with ongoing infection and/or presensitization, who are at high immunological risk but also vulnerable to infectious complications. The number of patients with renal impairment is also growing due to lengthening waiting times, intensifying the need for strategies that minimize calcineurin inhibitor (CNI) toxicity. Additionally, the importance of donor-specific antibodies (DSA) in predicting graft failure is influencing immunosuppressive regimens. In light of these developments, and in view of the lack of evidence-based prescribing criteria, experts from Germany, Austria, and Switzerland convened to identify indications for rATG induction in heart transplantation and to develop an algorithm for its use based on patient characteristics.